Filsafat Islam dan Tantangan Modernitas - Mujiburrohman, Mujiburrohman; Hadiwijaya, Lalu Firman (TSAQOFAH, 2025)
Islamic philosophy continues to face complex challenges of modernity, ranging from epistemological transformations due to the digital era to ontological shifts in understanding contemporary realities. This study explores how Islamic philosophy adapts to various modern issues, such as globalization, science, and secularization, while maintaining its normative essence. The research employs a library study method with a hermeneutic-philosophical approach to analyze the reconstruction of Islamic thought in response to contemporary challenges. The findings indicate that Islamic philosophy remains relevant through an integrative approach between tradition and innovation. The recontextualization of epistemological, ontological, and ethical concepts enables Islamic philosophy to address modern issues with a solution-oriented and forward-looking perspective. Thus, Islamic philosophy not only preserves its intellectual heritage but also contributes to the global discourse on ethics, humanity, and science.